Morphology of Thai edentulous mandible using 3D reverse engineering: Relevance to immediate loading dental implant design - Suthasinee Kasemsarn (2018)
The dimension and number of implants as well as the splinting concept of the super-structure are the impact factors of the immediate loading implant-supported prostheses. The purpose of this study is to determine the morphometric data of Thai lower edentulous jaws between two metal foramens for optimizing the design. Sixty-four Thai cadaveric edentulous mandibles were CT scanned and 3D models were reconstructed. Arch forms, dimensions, and the area of the greatest concavity in the body of the mandibles between the metal foramens were defined in geometric terms based on reverse engineering methods. The arch forms, represented by average values of angle and distance of panoramic arc, were 116.4 ± 9.5 degrees and 46.7 ± 3.9 mm respectively. The dimensions of the mandibles, determined by the height and width of the body of the mandibles as well as the angle between the axis of the mandibular body to the mandibular plane, were 25.3 ± 0.6 mm, 11.6 ± 0.6 mm and 61.3 ± 1.7 degrees respectively. The area of greatest concavity was 8.3 ± 1.9 mm. Morphology of the Thai edentulous mandible determines the maximum length of an implant placed for immediate loading protocol as 17 mm, with a maximum diameter of 3.5-5 mm. The maximum number of implants that can be placed in the anterior region is 5. Copyright © 2007 by The Japan Society of Mechanical Engineers.